Perceived health in a population based sample of victims of the 1956 polio epidemic in the Netherlands. Issue 6 (1st December 2002) - Nollet, F; Ivanyi, B; Beelen, A; de Haan, R J; Lankhorst, G J; de Visser, M
Abstract : Objective: To investigate perceived health and its relation to residual paresis from polio, late onset neuromuscular symptoms following poliomyelitis (LSP), and sex, in a population based sample of polio survivors. Methods: 350 subjects traced from the notification records of the Dutch 1956 polio epidemic received a mailed questionnaire on residual polio paresis and new neuromuscular symptoms. Perceived health was measured using the Nottingham health profile. Respondents with new muscle weakness and new neuromuscular symptoms were considered as cases with LSP. Results: Health problems were perceived by 151 of the 260 respondents. Respondents with residual paresis had significantly more health problems than clinically recovered respondents for the Nottingham health profile category of physical mobility. The perceived health of respondents with LSP (45.5%) was significantly worse than that of respondents without LSP for all the health profile categories. Among the respondents with LSP, health status did not differ between those with residual paresis and those who had recovered, except for physical mobility. Female respondents with LSP reported worse health status than male respondents with regard to physical mobility and social isolation. Conclusions: In this population based sample, health problems were frequently reported. They were mainly related to late onset neuromuscular symptoms following poliomyelitis, which were perceived by a substantial proportion of all polio survivors—not only subjects with polio residuals but also individuals who (subjectively) had recovered from polio.